2017
DOI: 10.1016/j.clinthera.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Risk Evaluation and Mitigation Strategies (REMS), Pemoline, and What Is a Signal?

Abstract: , MD, on the subject of pharmacovigilance and postmarketing surveillance. 1-5 In 2007 the Food and Drug Administration (FDA) was authorized to require sponsors to develop a Risk Evaluation and Mitigation Strategy (REMS) whenever there was a suspicion that more information might be needed to ensure the safety of a newly marketed product. 6 A REMS is an anticipatory risk management program intended to pick up unwanted drug effects once more patients are exposed to a drug than occurred during Phase II and III stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Consider the case of pemoline, a stimulant used to treat ADHD that was withdrawn from the US in 2005. After its withdrawal in the US, it was still available in Japan as a narcolepsy treatment (Shrader, 2017). In the US, not only was the use of pemoline withdrawn, but treating narcolepsy would be a side effect, where in Japan it was the intended effect.…”
Section: Intended V Unintendedmentioning
confidence: 99%
“…Consider the case of pemoline, a stimulant used to treat ADHD that was withdrawn from the US in 2005. After its withdrawal in the US, it was still available in Japan as a narcolepsy treatment (Shrader, 2017). In the US, not only was the use of pemoline withdrawn, but treating narcolepsy would be a side effect, where in Japan it was the intended effect.…”
Section: Intended V Unintendedmentioning
confidence: 99%
“…Using my six criteria, any of you who read my April 2017 Editor-in-Chief's Note will readily understand why I concluded that the observations linking pemoline and hepatic failure were not conclusive. 6 I feel that causality for that drug-ADR pairing was best classified as somewhere between possible and probable; it surely was not definite. Curiously, in a single-assessor evaluation using the Naranjo items as well as the World Health Organization's (WHO's) criteria to score 913 clinical reports on ADRs from a number of different drugs, causality was most frequently determined to be at the possible level on both scales.…”
mentioning
confidence: 99%